Urbanization and its implication on the Malay women's social interaction - Omar, Siti Zobidah; Abd Rahim, Normaliza; Zainon Hamzah, Zaitul Azma; Abdullah, Amini Amir (2008)
Over the past decades, Malaysia has seen a tremendous social and economic development. One of the developments is through the process of urbanization. With the implementation of the Malaysian New Economic Policy (NEP) from 1970 onwards, which specifically encouraged the involvement of the Bumiputeras, who are largely rural based, in the industrial and commercial sector of the economy, has a profound effect of the rate of urbanization in Malaysia. Rural areas are being developed and transformed to a new urban area. This process of transformation has an effect on the social interaction on the community in the area particularly the women. The aim of this paper is to examine the pattern of social interaction particularly on the Malay women’s communication in Malaysia, due to the process of development and urbanization in their area. Further, it is also intended to look at the women’s view on the meaning of urbanization, its implication towards their pattern of communication and their experience of having the telephone at home. This research employs a qualitative method by using an in-depth interview of fifteen Malay women, who live in the area that has undergone and experienced the process of urbanization. The selection of the informant was through snowballing. The research revealed that due to the rapid development, there is a changing pattern in the women’s social interaction particularly their communication. This communication changing pattern has led the women to change their way of communication that is by using Information Communication Technology (ICT) particularly the telephone to replace their daily face-to-face communication. The research also revealed the women’s story of their first experience of having the telephone at home and how they communicate with others. The research conclude that the meaning of urbanization to the women is apart from enables them to communicate easily via new technology, it is also seen as trying to separate the women among themselves physically, living them to communicate in isolation.